2007
DOI: 10.3324/haematol.10455
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance imaging R2* assessments and analysis of historical parameters in patients with transfusion-dependent thalassemia

Abstract: Recent advances in magnetic resonance imaging (MRI) techniques allow the assessment of iron overload in tissues 1 especially the heart, 2 in transfusion-dependent thalassemia patients. The R2* value (1/T2*) recorded in the intraventricular septum of the heart indirectly measures the degree of cardiac iron load. Applying this new technology we looked at a number of historical and biochemical parameters in order to determine their relationship to cardiac iron overload and the effect of cardiac iron on functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 6 publications
5
77
3
3
Order By: Relevance
“…This matches the low predictive value of most forms of ferritin measurements. 13 We also confirmed that pancreatic hemosiderosis did not correlate with liver hemosiderosis. 8 However, there was strong correlation between hemosiderosis of the pancreas and heart.…”
Section: Resultssupporting
confidence: 74%
“…This matches the low predictive value of most forms of ferritin measurements. 13 We also confirmed that pancreatic hemosiderosis did not correlate with liver hemosiderosis. 8 However, there was strong correlation between hemosiderosis of the pancreas and heart.…”
Section: Resultssupporting
confidence: 74%
“…7 Our data confirmed that liver MRI is not useful to predict heart failure, 5,8 and further showed that it cannot predict endocrine failures. Cardiac MRI T2*, however, was useful in predicting both heart and endocrine failures.…”
supporting
confidence: 74%
“…Cross sectional analysis has demonstrated a poor correlation between the cardiac T2* value and the LIC in the literature (10,31,32). Despite the significant negative correlation between the heart T2* value and the liver R2 value, the correlation was weak, with a wide scatter of values, indicating that cardiac T2* measurement is essential for predicting cardiac complications and the associated risk of death.…”
Section: Discussionmentioning
confidence: 95%